Effect Service Quality and Promotion on Consumer Satisfaction Toyota Agya Sutomo Pekanbaru - Novelia, Sindy; Sutrisna, Endang; Mandataris, Mandataris (ProBisnis : Jurnal Manajemen, 2025)
Indonesia is an automotive manufacturer that provides automotive products from low price to premium class. Toyota is one of the automotive brands in Indonesia that is in great demand by consumers. The type of car that is the choice of consumers from the many types of cars in Indonesia is the Low Cost Green Car (LCGC) type car. One of the Low Cost Green Car products from the Toyota brand that is in great demand by consumers is the Toyota Agya. Based on Low Cost Green Car (LCGC) sales data obtained in 2023, Toyota Agya experienced a decline in sales at PT Agung Automall Pekanbaru Sutomo Branch, this is known based on data in 2023 Toyota Agya sales of 20,602 units. This is much lower than sales in 2022, as many as 21,336 units. Based on this phenomenon, PT Agung Automall Sutomo Branch made efforts to improve Service Quality and also offered various promotions to consumers. Based on the results of the study, it shows that the Quality of Service and Promotion carried out by PT Agung Automall Sutomo Branch was well validated.